Identification of key molecular targets for stachyose in hepatocellular carcinoma: focus on STAT3 and FN1 - Chen, Haihua; Wang, Xianyou; Ying, Jiongcheng; Huang, YuQin; Liu, Yuxi; Feng, Yifu; Fang, Binbo (Frontiers in Oncology, 2025)
Background and objectiveHepatocellular carcinoma (HCC) ranks among the most prevalent malignancies on a global scale. Stachyose (STA), an oligosaccharide widely present in legumes, has demonstrated various biological activities, including improving gut microbiota, anti-oxidative stress, and anti-tumor proliferation. This study aimed to predict potential targets of STA in HCC treatment and to identify key hub genes.MethodsBy integrating multiple public databases and bioinformatics tools, we screened 34 candidate targets and constructed STA’s action network and PPI network in HCC. Functional enrichment analysis revealed 10 relevant KEGG pathways and key features related to cellular components, molecular functions, and biological processes. Finally, we conducted molecular docking, single gene analysis, and in vitro experimental validation on core targets.ResultsThrough screening of multiple databases, we identified 34 common targets associated with STA and HCC and subsequently constructed a protein-protein interaction (PPI) network. Through this analysis, we ultimately selected STAT3 and FN1 as core hub genes. Functional and pathway analyses indicated that these targets participate in multiple cancer-related pathways and have significant roles in cellular components, biological processes, and molecular functions. The results indicated a positive correlation between the expression of STAT3 and FN1 with angiogenesis, tumor inflammation, and epithelial-mesenchymal transition (EMT). Molecular docking experiments validated the stable binding capacity between STA and these core genes, and in vitro experiments further confirmed that STA could inhibit HCC cell proliferation and migration by downregulating STAT3 and FN1 expression.ConclusionThis study offers a comprehensive exploration of the molecular mechanisms through which STA may treat HCC, identifying STAT3 and FN1 as key targets and validating their clinical relevance and potential for application.